2017
DOI: 10.3389/fphar.2017.00419
|View full text |Cite
|
Sign up to set email alerts
|

Sophisticated Cloning, Fermentation, and Purification Technologies for an Enhanced Therapeutic Protein Production: A Review

Abstract: The protein productions strategies are crucial towards the development of application based research and elucidating the novel purification strategies for industrial production. Currently, there are few innovative avenues are studies for cloning, upstream, and purification through efficient bioprocess development. Such strategies are beneficial for industries as well as proven to be vital for effectual therapeutic protein development. Though, these techniques are well documented, but, there is scope of additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 137 publications
(242 reference statements)
0
38
0
Order By: Relevance
“…Additional favorable microbial recombinant protein production systems are the eukaryotic microorganisms S. cerevisiae and P. pastoris . Both of these hosts are capable of producing recombinant proteins with proper folding and posttranslational modifications .…”
Section: Systems For the Production Of Biopharmaceuticalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional favorable microbial recombinant protein production systems are the eukaryotic microorganisms S. cerevisiae and P. pastoris . Both of these hosts are capable of producing recombinant proteins with proper folding and posttranslational modifications .…”
Section: Systems For the Production Of Biopharmaceuticalsmentioning
confidence: 99%
“…The S. cerevisiae yeast expression system is frequently used due to their rapid growth in protein‐free media and ability to secrete the product extracellularly. However, posttranslational modifications that occur within the cells often lead to the production of undesired hypermannosylation , which can result in altered protein binding activity, and potentially yield an altered immunogenic response in therapeutic applications. In P. pastoris , oligosaccharides have much shorter chain lengths and the strain has been reported to produce complex, terminally sialylated or “humanized” glycoproteins .…”
Section: Systems For the Production Of Biopharmaceuticalsmentioning
confidence: 99%
“…Recent work has suggested that this is not necessarily always the case, with the identification and introduction of a key regulatory element (the nonclustered LuxR‐type quorum‐sensing receptor, PviR, from P. luteoviolacea 2ta16) into E. coli increasing pathway transcription and production of violacein—a proof of concept compound—by ≈60‐fold . This work makes a case for identification of other regulatory elements which may increase the feasibility of E. coli in use for heterologous expression of antibiotic biosynthetic gene clusters, although it does not account for the level of metabolic burden associated with large heterologous proteins expressed in E. coli , as well as the organism's poor capacity for secretion …”
Section: Chassismentioning
confidence: 99%
“…Escherichia coli has been used to produce recombinant proteins because it can be easily cultured and is amenable to genetic modification. However, the production of recombinant proteins using this system is hampered by a lack of post-translational modifications (PTMs) and the risk of endotoxin contamination [5]. Recombinant proteins are also frequently produced in yeasts, such as Saccharomyces cerevisiae and Pichia pastoris .…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant proteins are also frequently produced in yeasts, such as Saccharomyces cerevisiae and Pichia pastoris . Although yeast cells can be easily and inexpensively cultured, this approach is restricted by the limited number of yeast vectors and promoters as well as the lack of PTMs observed in human cells [5, 6]. Production of recombinant proteins in animal cells is a promising alternative with various clinical applications.…”
Section: Introductionmentioning
confidence: 99%